(untitled) (Research, Society and Development, 2022)
Bibliometrics represents an important resource for diagnosing and monitoring the dissemination of scientific knowledge in a given area. This research aimed to typify the profile of scientific publications in the area of endodontics in two high impact journals. To this end, articles published between January 2011 and December 2020 in the International Endodontic Journal and the Journal of Endodontics were evaluated and characterized according to the methodological type and nationality of the main author. A total of 4335 articles were published in both journals in the decade evaluated. Basic technology research articles represented 36.6% of productions and only 2.9% were published using a systematic review methodology. Most of the research came from Brazil (20.2%), followed by the United States of America (15.0%) and China (8.2%). The vast majority of publications were classified as basic research in biology or technology. In addition, Brazil is the largest producer of high-impact publications on endodontics between 2011 and 2020.